L’enquête de l’Institut International d’Agriculture sur la réutilisation des déchets et des résidus (1920-1922) ou qui gouverne l’agriculture ? - Niccolò Mignemi (Journal for the History of Environment and Society, 2017)
The International Institute of Agriculture (IIA) set up an enquiry in 1920 on the technical solutions and legislative measures adopted by various governments during and after the First World War, with a view to intensifying agricultural production. One particularly interesting aspect of this vast research programme was the reuse of urban and industrial waste in the countryside, as food or fertiliser. Although the rest of the enquiry was slow to take shape, this section became the subject of a specific study entrusted to Arturo Bruttini, the IIA librarian, an outstanding member of his generation of Italian agronomists. The results of this enquiry appeared as a monograph in French, English and Italian editions (1922-1923). This article is mostly concerned with the problems that arose when the enquiry was being set up; this allows us to trace the IIA’s concerns in the post-war conditions. Not only was it having difficulty establishing its claim to authority with its member states but it was also obliged to renegotiate its place in the new balance of power created when the League of Nations and the International Labour Organization were set up. Analysing the content of the enquiry thus provides an opportunity to examine in a transnational perspective how issues evolved at the very centre of international agricultural regulation. The IIA study was conceived as a synthesis of a great variety of earlier studies and proceeded by bringing together a mass of information and data on the scientific, technical, economic and legislative aspects of recycling from all the countries of the world. Agronomic knowledge was presented as applied knowledge to be used to modernise existing practices and popularise technical change. The article takes up two themes to do with this topic: the links between agriculture and industry and the relations between rural and urban. The IIA enquiry was also interested in the legislative and administrative aspects of reusing waste materials. This provided an opportunity to examine the changing role of the State in managing agriculture and the solutions that the IIA offered for national economies faced during the inter-war years with new equilibriums in both the producing sectors and in international trade.